Administrative Archiving Management Information System Through SITATA in Pascasarjana IAIN Palangka Raya - Rahmad Wahyudi; Maulina Maulina; Haji Abdul Karim; Abdul Qodir; Musyarapah Musyarapah (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2023)
Based on the author's result of observations, Pascasarjana Institut Agama Islam Negeri (IAIN) Palangka Raya faced problems in the management of archiving administrative documents, namely inadequate archive space and taking too long time to look for a document in a particular case. So the author designed and built an information system named Administrative Information System (literally Sistem Informasi Ketatausahaan (SITATA)) in order to overcome these administrative archiving management problems. This research aims to explain the design and implementation of SITATA. The method used in this study is the waterfall technique. This information system, which was designed withcode using PHP as the programming language and MySQL as the database, it could be accessed offline via the local host web server XAMPP. This information system can add, edit, delete, save, search, recap, and print archived documents. The results obtained from the implementation of this information system are that it makes it easier for Pascasarjana IAIN Palangka Raya in managing letter archiving although it still needs further improvement.